TOTAL VOLUMETRIC MASS TRANSFER COEFFICIENT AT CO2 GAS ABSORPTION USING K2CO3 BY MSG PROMOTER - Ningsih, Erlinda; Sato, Abas; Nafiuddin, Mochammad Alfan; Putranto, Wisnu Setyo (Konversi, 2018)
Abstract- One of the most widely used processes for CO2 gas removal is Absorption. Carbon dioxide is the result of the fuel combustion process which of the hazardous gases. The aim of this research is to determine the total mass transfer coefficient and analyze the effect of the absorbent flow rate of the absorbent solution with the promoter and the gas flow rate to the total mass transfer coefficient value. The variables consisted of liquid flow rate: 1, 2, 3, 4, 5 liter/min, gas flow rate: 15, 25, 30, 40, 50 liter/min and MSG concentration: 0%, 1%, 3% and 5% by weight. The solution of Pottasium Carbonate as absorbent with MSG promoter is flowed through top column and CO2 gas flowed from bottom packed column. Liquids were analyzed by titration and the gas output was analyzed by GC. From this research, it is found that the flow rate of gas and the liquid flow rate is directly proportional to the value of KGa. The liquid flow rate variable 5 liters / minute, gas flow rate 15 l / min obtained value of KGa 11,1102 at concentration of MSG 5%. Keywords:  Absorption, CO2,  K2CO3, MSG.